Experiences of veterans with spinal cord injury related to annual urine screening and antibiotic use for urinary tract infections. Issue 12 (22nd July 2021) - Hines‐Munson, Casey; May, Sarah; Poon, Ivy; Holmes, S. Ann; Martin, Lindsey; Trautner, Barbara W.; Skelton, Felicia
Abstract: Introduction: Antimicrobial‐resistant bacterial infections are an increasing public health threat and people with spinal cord injury (SCI) are disproportionally at higher risk. National guidelines concerning urine testing after SCI are conflicting. Unnecessary urine testing in the SCI population (with high asymptomatic bacteriuria prevalence) leads to unnecessary antimicrobial use, propagating resistant infections, especially urinary tract infections (UTIs). Objectives: (a) Describe UTI antimicrobial adherence in patients with SCI. (b) Explore SCI patient knowledge and attitudes toward current urine testing and treatment practices. Design: Mixed methods. Setting: Veterans Health Administration (VHA) patients with SCI. Participants: Veterans identified as having SCI seen at a VHA facility nationwide. Interventions: N/A. Main Outcome Measures: Self‐reported medication adherence, patient beliefs and behaviors toward UTIs and antimicrobial use. Results: A total of 105 Morisky Medication Adherence Scale‐8 (MMAS‐8) surveys were completed out of 369 distributed surveys (28% response rate). Overall, patients reported high medication adherence (mean score of 7.2/8, with 8 being a perfect adherence score). Ten qualitative interviews were completed. Themes identified include generally high adherence to prescribed antimicrobial courses and high levels of patient satisfaction with current outpatient VHA SCI bladder care. The quantitative findings converge with these themes observed in the qualitative interviews; patients were satisfied with current urine testing and treatment practices. Conclusions: Veterans with SCI are generally satisfied with their current UTI management and self‐report taking antimicrobials for UTIs as prescribed. Veterans with SCI typically report high trust in their SCI providers and value their advice on bladder care management. Therefore, it is imperative for clinicians to provide evidence‐based education to patients, as well as ensure that each prescribed course of antibiotics for UTI is clinically necessary. Information from this study will guide an intervention promoting appropriate urine testing and antimicrobial prescription practices by SCI providers.